Pharmaceutical laws and regulations in Iran: An overview - Pardis Zaboli; Amir Hashemi-Meshkini; Mehdi Varmaghani; Hadi Gholami; Iman Vazirian; Hedieh-Sadat Zekri; Shahriar Eslamitabar; Abbas Kebriaeezadeh (Journal of Research in Pharmacy Practice, 2016)
The pharmaceutical legal framework is a very important infrastructure in achieving predefined goals in pharmaceutical sector: Accessibility, quality, and rational use of medicine. This study aims to review the current pharmaceutical sector-related legal provisions in Iran where the Food and Drug Organization (FDO) is in charge of regulating all issues related to the pharmaceutical sector. The main laws and regulations enacted by parliament and cabinet and even internal regulations enacted by the Ministry of Health or Iran FDO are reviewed. Different laws and regulations are categorized according to the main goals of Iran national drug policy.